The Influence of Digital Personal Branding Strategy and Supporting Political Party Reputation on the Electability of DPR-RI Legislative Candidates Mediated by Public Trust - Yamin, Bun; Nurfadilah, Mursidah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to determine the effect of Digital Personal Branding Strategy and the Reputation of Supporting Political Parties on the Electability of DPR-RI Candidates, mediated by Public Trust. The research adopts a quantitative approach with an associative design to examine the relationship between the Digital Personal Branding Strategy (X1), Political Party Reputation (X2), Electability (Y), and Public Trust (Z) as a mediating variable. The purpose of this research is to develop hypotheses that can be used to predict, explain, and manage specific conditions. A quantitative approach is used to obtain numerical data from the measurement of the study's variables. The sample for this study consisted of 100 respondents who had exercised their voting rights in the election of DPR-RI candidates in Malang. The data analysis stage involves identifying the relationships between the variables under study and evaluating their influence, with a focus on the effects of the Digital Personal Branding Strategy and Political Party Reputation on Candidate Electability, as mediated by Public Trust. The results of this study provide a better understanding of the factors that influence the electability of legislative candidates, highlighting the importance of public trust and digital personal branding strategies in the political context.